A method of obtaining the preliminary estimates of the parameters of seazonal growth models - Junior, Paulo Silveira; Zonta, Élio Paulo; Machado, Amauri Almeida; Costa, Ricardo F. de Sousa (Pesquisa Agropecuaria Brasileira, 1992)
A method of abtaining the preliminary estimates (inicial values) of the parameters of non-linear models of seazonal growth is presented. The method is applied to the Bertalanffy cubic root model with seazonal components. An illustration is provided through an application of the method to the analysis of growth of weight data of bovines of the Ibagé race and of buffaloes of the Murrah race.
Keywords: Bertalanffy cubic root; growth curves; non-linear models